Chang'e-2 spacecraft observations of asteroid 4179 Toutatis. Issue Volume 10:Issue S318(2015) (1st March 2016) - Ji, Jianghui; Jiang, Yun; Zhao, Yuhui; Wang, Su; Yu, Liangliang
Abstract: On 13 December 2012, Chang'e-2 completed a successful flyby of the near-Earth asteroid 4179 Toutatis at a closest distance of 770 meters from the asteroid's surface. The observations show that Toutatis has an irregular surface and its shape resembles a ginger-root of a smaller lobe (head) and a larger lobe (body). Such bilobate shape is indicative of a contact binary origin for Toutatis. In addition, the high-resolution images better than 3 meters provide a number of new discoveries about this asteroid, such as an 800-meter depression at the end of the large lobe, a sharply perpendicular silhouette near the neck region, boulders, indicating that Toutatis is probably a rubble-pile asteroid. Chang'e-2 observations have significantly revealed new insights into the geological features and the formation and evolution of this asteroid. In final, we brief the future Chinese asteroid mission concept.